ANALISIS PROFITABILITAS PT. HOLCIM INDONESIA, TBK. - Budi, Heri Setya (EKONOMIA, 2012)
Analysis of the financial statements presents the key indicators of the company's financial condition. One of the tools of financial ratio analysis is profitability ratios. Profitability is of significant importance in the effort to survive in the long term, because the profitability indicates whether the entity has a good prospect in the future.Â By using profitability ratios can be seen that the increase in value does not automatically make a profit profitability also increased the financial statements, it is influenced also by other factors such as sales, cost of sales and total assets of the company.Â Keywords: Profitability, profit, asset, Sold, Cost of Goods Sold.